Vloga geografije pri interdisciplinarnem načrtovanju regionalnega razvoja - Lorber, Lučka (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
The characteristic of the science of geography is its complexity in the study of space. Regional development processes are integral and we can understand and evaluate them through interdisciplinary approaches. The role and significance of geography in planning regional development in changed social -economic conditions is in cooperation with the remaining scientific disciplines in assuring comformable regional development.
Keywords: ecology; ekologija; geografija; geography; regionalni razvoj; Slovenia; Slovenija; sonaravni razvoj; sustainable development; trajnostni razvoj